Elite quarterbacks do not laugh when they are losing: Exploring fan responses to athletes' emotional displays - Sanderson, J. (International Journal of Sport and Exercise Psychology, 2016)
Athletes experience a multitude of emotions during sport competition. How they manage and regulate emotions is, to some degree, influenced by social expectations. This research explored how fans framed emotional expressions by National Football League quarterback Derek Anderson during and after a Monday Night Football game. A thematic analysis of 304 postings in an ESPN.com discussion forum was conducted. Results revealed that fans viewed Anderson's emotional expressions as: (a) appropriate behaviour; (b) lack of professionalism; and (c) a character flaw. The results suggest that fans hold inconsistent expectations about athletes` emotional displays and that these shifting preferences place athletes in complex positions as they attempt to manage and regulate their emotions before, during, and after sporting events.